Implementasi Metode Index Time Series Untuk Menilai Kinerja Keuangan PT Aneka Tambang Tbk Yang Terdapat Di BEI Tahun 2020-2024 - Zannuba, Eka Ulviana; Indriyani, Furi; Napitupulu, Rohani Lestari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstracts - This study aims to analyze the financial performance of PT Aneka Tambang Tbk (ANTAM) during the 2020–2024 period using the Index Time Series (ITS) method. The analysis focuses on liquidity, solvency, and profitability ratios based on the company’s annual financial statements. The results indicate significant fluctuations in net income, total assets, and other financial components. These changes were influenced by internal factors, such as operational strategies and cost efficiency, as well as external factors, including the impact of the COVID-19 pandemic and a corruption case that temporarily affected the company. Overall, the solvency ratio showed an increasing trend, reflecting the company’s improved ability to meet long-term obligations. In contrast, profitability ratios tended to decline in the later years, signaling pressure on the company’s ability to generate consistent profits. This study provides a comprehensive overview of ANTAM’s financial performance dynamics over the past five years. The findings are expected to serve as a reference for management in formulating more effective strategic policies and as a useful consideration for investors in making informed investment decisions.